Analysis of Physics Laboratory Management at The Northern Region of Makassar’s State Senior High Schools By Standard of Facilities and Infrastructure - Anggereni, Santih; Ikbal, Muh. Syihab (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2018)
This research is descriptive research that aims to know: 1). Description of physics laboratory management related to the layout based on the standard of facilities, 2). The description of the management of physics-related physics laboratory based on the standard of facilities, and 3). Description of the management of the physics laboratory related to safety and health based on the standard of facilities and infrastructure. The population of this research was six state senior high schools (SMAN) in the north region of Makassar. Three samples were obtained by purposive sampling. The results Showed that the management of the layout of the physics had met the standard. Spatial Management of the laboratories was categorized as less appropriate with the standards. Occupational Health and safety (OHS) is categorized as less appropriate with the standards. Based on the results obtained it can be concluded that only in the aspect of the management of the physics laboratories' layout is in line with the regulation of the Ministry ofNational Education No.24, 2007.